Phytoremediation of Arsenic-Contaminated Soils Amended with Red Mud Combined with Phosphogypsum - de Souza Costa, Enio Tarso; Lopes, Guilherme; Carvalho, Geila Santos; Penha, Henrique Gualberto Vilela; Curi, Nilton; Guilherme, Luiz Roberto Guimarães (Water, air, and soil pollution, 2021)
Several industrial by-products may be used as amendments to reduce arsenic availability in contaminated areas, hence contributing to phytoremediation processes. This study was conducted aiming to evaluate red mud (RM) and a mixture containing 75% of RM + 25% of phosphogypsum (PG) (hereafter, RMPG) as amendments in arsenic-contaminated soils presenting distinct properties, like clay and organic matter content and chemical composition. Two contrasting soils were artificially contaminated with 150 mg dm 3 of arsenic and after that cultivated with Urochloa brizantha . The experiment was carried out using a Typic Dystrudox (LV, 750 g kg −1 clay) and a Typic Quartzipsamment (RQ, 70 g kg −1 clay), with the following RM and RMPG rates: 0, 0.5, 1.0, and 2.0% (w/v). Also, limestone was tested as an additional amendment for comparison. Hydrogen potential (pH), electrical conductivity (EC), sodium, and arsenic concentrations were analyzed on leachates, and the dry matter production of Urochloa brizantha and arsenic concentration in plant root and shoot dry matter were also recorded. The amendments increased pH, EC, and sodium concentration and the addition of RMPG decreased the arsenic concentration on leachates. RMPG increased plant dry matter production and decreased arsenic concentration in the plant’s shoot. The plant resistance to arsenic contamination was influenced by soil properties, with arsenic toxicity being more evident in the sandy soil (RQ) compared with the clayey soil (LV). The mixture (RMPG) has shown to be an advantageous amendment since, besides decreasing arsenic availability, it also furnishes the nutrients calcium and sulfur from the PG. Graphical abstract